HEGEL’S COMPREHENSION THE UNITY OF CONTRASTS AT ITS RECONCILIATION THROUGH COMPROMISES ITS - Лагетко, В. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
Hegel’s dialectics appear the world through the absolute Idea as the unity contrasts which our world is. Contrasts in this unity can be only the things which they are anticipating and denying itself. Such state of things, unity of contrasts, at its reconciliation it is possible through compromises which we can research, as G.W.F. Hegel.